RISK CONTROL STRATEGIES FOR RED CHILI SEED PRODUCTION - Intan Pujiarti; Djoko Koestiono; Anisa Aprilia; Riska Ayu Febriana (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
The purposes of this study were to identify risk components, determine the priority of risk components and formulate a strategy for controlling priority risk components at each stage of the red pepper seed production process. Fuzzy FMEA (Failure Mode Effects Analysis) and AHP (Analytical Hierarchy Process) were used in this study. The findings of the study showed that production risk has 15 risk components from 6 variables. The highest risk components for each of the red chilli seed production processes, namely, failure in the nursery, seedlings die after planting, changing weather conditions, rotten chilli, damage to the seed release machine and chilli seed moisture content are not according to the standard. AHP calculation results obtained the highest value weighting on the criteria, namely maintenance. An alternative control strategy that has the highest weighting value was caring and maintaining the production environment.